Co-designing an mHealth tool in the New Zealand Māori community with a "Kaupapa Māori" approach. (March 2018) - Te Morenga, Lisa; Pekepo, Crystal; Corrigan, Callie; Matoe, Leonie; Mules, Rangimarie; Goodwin, Debbie; Dymus, Janelle; Tunks, Megan; Grey, Jacqui; Humphrey, Gayl; Jull, Andrew; Whittaker, Robyn; et al.
Obesity rates in Aotearoa/New Zealand continue to rise, and there is an urgent need for effective interventions. However, interventions designed for the general population tend to be less effective for Māori communities and may contribute to increased health inequities. We describe the integration of co-design and kaupapa Māori research approaches to design a mobile-phone delivered (mHealth) healthy lifestyle app that supports the health aspirations of Māori communities. The co-design approach empowered our communities to take an active role in the research. They described a holistic vision of health centred on family well-being and maintaining connections to people and place. Our resultant prototype app, OL@-OR@, includes content that would not have been readily envisaged by academic researchers used to adapting international research on behaviour change techniques to develop health interventions. We argue that this research approach should be considered best practice for developing health interventions targeting Māori communities in future.